2020
DOI: 10.1007/s12553-020-00502-w
|View full text |Cite
|
Sign up to set email alerts
|

Applying software-defined networking to support telemedicine health consultation during and post Covid-19 era

Abstract: The novel coronavirus disease-19 (COVID-19) infection has altered the society, economy, and entire healthcare system. Whilst this pandemic has presented the healthcare system with unprecedented challenges, it has rapidly promoted the adoption of telemedicine to deliver healthcare at a distance. Telemedicine is the use of Information and Communication Technology (ICT) for collecting, organizing, storing, retrieving, and exchanging medical information. But it is faced with the limitations of conventional IP-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Previous studies on telemedicine during the COVID-19 pandemic have focused on applications that include, forward triage [12], automated logic flows (bots) [12], management of chronic conditions [13], mental health services [14], palliative care [15] and teleneurology [16]; challenges, that include, coordination and integration of involved sectors [12,17,18], creation of regulatory frameworks [4,13,[17][18][19], accessibility to mobile technologies [20]; reviews [21,22]; suggestions of a Software-Defined Network architecture for telemedicine purposes [23]; suggestions on potential benefits of using telemedicine for vulnerable groups that do not have access to clinical services due to COVID-19, such as gestant women from developing countries, as pregnancy has been reported as a clinical condition with risk factors [24,25]; discussions on the legislation of telemedicine as its adoption has become increasingly widespread and new legislation frameworks will need to be developed to satisfy this new demand [26]; discussions about lessons of operationalizing telemedicine in ophthalmology and its potential effect for health systems [27,28]; propositions of models of clinical attention that consisted in a mix of in-person visits with telemedicine support [29]; discussions of solutions for long-term COVID-19 consequences that can include telemedicine support [30]; propositions of offering telehealth service in public spaces as a form to prevent the intimated partner violence (IPV), as it has been reported that this situation has been increased during the pandemic COVID-19 due to the process of lockdown [31]; studies of the impact of COVID-19 of clinical trials which concluded that the pandemic has damaged the quality of the studies [32].…”
Section: Plos Onementioning
confidence: 99%
“…Previous studies on telemedicine during the COVID-19 pandemic have focused on applications that include, forward triage [12], automated logic flows (bots) [12], management of chronic conditions [13], mental health services [14], palliative care [15] and teleneurology [16]; challenges, that include, coordination and integration of involved sectors [12,17,18], creation of regulatory frameworks [4,13,[17][18][19], accessibility to mobile technologies [20]; reviews [21,22]; suggestions of a Software-Defined Network architecture for telemedicine purposes [23]; suggestions on potential benefits of using telemedicine for vulnerable groups that do not have access to clinical services due to COVID-19, such as gestant women from developing countries, as pregnancy has been reported as a clinical condition with risk factors [24,25]; discussions on the legislation of telemedicine as its adoption has become increasingly widespread and new legislation frameworks will need to be developed to satisfy this new demand [26]; discussions about lessons of operationalizing telemedicine in ophthalmology and its potential effect for health systems [27,28]; propositions of models of clinical attention that consisted in a mix of in-person visits with telemedicine support [29]; discussions of solutions for long-term COVID-19 consequences that can include telemedicine support [30]; propositions of offering telehealth service in public spaces as a form to prevent the intimated partner violence (IPV), as it has been reported that this situation has been increased during the pandemic COVID-19 due to the process of lockdown [31]; studies of the impact of COVID-19 of clinical trials which concluded that the pandemic has damaged the quality of the studies [32].…”
Section: Plos Onementioning
confidence: 99%
“…[6][7][8] Likewise, telemedicine, virtual software, and virtual care are useful tools of information and communication technologies (ICT) for the remote treatment of COVID-19 patients. [9][10][11] These digital technologies are universal in scope and minimize the exposure of patients and physicians to the COVID-19 virus. In this regard, the global penetration of ICT around the world related to the smartphone area in 2019 was 3.2 billion users, and it is projected to reach 3.8 billion in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…According to International Energy Agency IEA (2020a), the temporal shut down of industrial sectors in countries due to the tight lockdown has resulted in low demand for electricity which has fallen by 5% to 10%, especially in European countries such as Spain, Italy, and so on. This raised the need for electricity operators needed to balance the demand and supply of energy (Chen et al, 2020;Jnr et al, 2020b;Jnr et al, 2020a). Since the renewable energies are largely unaffected, their demand has increased (IEA 2020b).…”
Section: Impact Of Covid-19 On Renewable Energy Sectormentioning
confidence: 99%